Field study on the transportation characteristics of PFASs from water source to tap water. (15th June 2021) - Chen, Ruya; Li, Guiwei; He, Yitian; Pan, Linlin; Yu, Ying; Shi, Baoyou
Highlights: Raw water pipelines can remove a certain extent of long-chain PFASs. Long-distance, open-channel water diversion can increase PFAS contamination risk. O3 -BAC and UV treatment processes can provide a certain removal effect on PFASs. The PFAS distribution is affected by the loose deposit in branched DWDSs. The PFAS concentration forms a relatively uniform distribution in the looped DWDSs. Abstract: Perfluoroalkyl substances (PFASs) can occur in water sources, pass through drinking water treatment plants (DWTPs), drinking water distribution systems (DWDSs), to the consumer taps. This investigation was carried out to present the transportation behaviors of 17 PFASs, involving seven DWTPs with different water sources, raw water transportation modes, treatment processes, and DWDS structures in eastern and northern China. The results showed that the long-distance raw water transportation pipelines removed a certain extent of PFASs from raw water, probably due to the accumulation of loose deposits. The long-distance, open-channel South-to-North water diversion increased PFAS contamination risk. In the DWTPs, granular activated carbon (GAC) adsorption and ultraviolet radiation removed less than 25% of PFASs, but ozonation-biological activated carbon (O3 -BAC) was superior to GAC alone in removing PFASs. Loose deposits couldsignificantly influence PFAS accumulation and release within branch-structured DWDSs. In loop-structured DWDSs, finished water with different PFAS characteristics could mix along the pipeline, with the corresponding DWTP as the center, ultimately forming a relatively uniform distribution in the entire DWDS. Graphical abstract: Image, graphical abstract